Prediction Models for Timber Weight of Populus deltoides Planted on Farmlands in Haryana - Rizvi, R.H.; Khare, Diwakar (Indian Journal of Agroforestry, 2020)
Poplar (Populus deltoides) is widely grown by farmers in Haryana as agroforestry crop because of short rotation and multipurpose use. The wood based industries especially the plywood industry requires the Poplar wood raw material in fresh green condition. In orderto estimate the fresh green timber of Poplar tree, growth process based non-linear models for fresh timber weight were evaluated. The models viz.; W = 1.398D1.608 and W = 9.975 exp(1+7.768 exp(-1.299 (D2H)-0217);Where W- fresh timber weight, 0- diameter at breast height and H- height of the tree, wasfound to be good fit. The mean errors in prediction of timber weight by these models were 10.4 and 7.0 Kg, respectively. Fresh timber weight table based on second model has also been prepared for use in Haryana.